The Effect of Make a Match Technique on Students’ Vocabulary Mastery - Ima, Dwi Sinta Mardiana; Huda, Tanzil; Mardiyana Devanti, Yeni (English Education Program, Education Faculty, Universitas Nurul Huda, 2024)
The purpose of this study is to determine the effect of the Make a Match Technique on students' vocabulary mastery at SMPN 1 Panti Jember in the academic year 2022/2023. This study employed a quasi-experimental design with a pre-test post-test non-equivalent control group. The population was seventh grade consist of 186 students and the sample of this research was seventh grade consist of 58 students of class E and F. The data were collected by using pre-test and post-test in control class and experimental class were analyzed using SPSS 16.0. The mean score of experimental class before giving the treatment is 72,30 and the mean score after giving the treatment is 87,40. For testing the hypothesis is used mann-whitney test as a substitute independent test, and the result is Sig. (2-tailed) 0,000 < 0,05. So, the Ha is accepted and H0 is rejected. Additionally, the result of data analysis shows that there is a significant effect on students’ vocabulary mastery who taught using Make a Match Technique. Using the Make a Match technique can also stimulate students to remember vocabulary better, especially in nouns and verbs.